Effect of synthesis parameters on cobalt oxide nanostructures morphology - Hoang, Thi Lan Anh; Nguyen, Minh Trung; Do, Thi Kieu Anh; Dang, Le Thi Thanh; Tran, Vu Diem Ngoc; Do, Thi Ngoc Tram; Nguyen, Duc Hoa (Communications in Physics, 2023)
A facile approach was employed for the synthesis of cobalt oxide nanorods (NRs) using cobalt nitrate, sodium oxalate and ethylene glycol as precursors via a hydrothermal process. The hydrothermal conditions, such as temperature and time, were varied to optimize the morphological characteristics of the NRs. After undergoing filtration, washing, and drying, the resulting material was characterized using several techniques, including field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and transmission electron microscopy (TEM). Our findings reveal that the NRs exhibit diverse morphologies, depending on the hydrothermal conditions, with the smallest aspect ratio observed when prepared at 200 °C for 24 hours. In addition, we investigated the gas sensing capabilities of the NRs to ammonia under these conditions.